Analysis on cooperative working performance of curtain wall glass and steel hanging columns. Issue 1 (March 2020) - Gong, Ke; Luan, Wei; Yang, Xiwen; Zhou, Yuyang
Abstract: The curtain wall of Xi'an Silk Road International Conference Center is a large-span combined steel column supported glass curtain wall system. The curtain wall glass is directly installed on the steel hanging columns of the external suspension structure, and there are no curtain wall hanging columns that are independent of the main structure. The vertical, tangential and radial deformation of the steel hanging columns under service load may lead to vertical shear, in-plane extrusion, in-plane sliding and out of plane bending of the curtain glass. Therefore, finite element model of curtain wall glass was established using the finite element program ABAQUS. Considering the four possible failure modes of the curtain glass, the collaborative working performance of the curtain wall glass under the most unfavourable deformation conditions of steel hanging columns was analyzed.